Incorporating Acupuncture Into American Healthcare: Initiating a Discussion on Implementation Science, the Status of the Field, and Stakeholder Considerations - David W. Miller MD, LAc; Eric J. Roseen DC, MSc; Jennifer A.M. Stone LAc; Paula Gardiner MD; Juli Olson DC, LAc; Shellie Rosen LAc; Peter Wayne PhD; Robert Davis LAc; Remy Coeytaux MD, PhD (SAGE Publishing, 2021)
Introduction The field of implementation science is the study of methods that promote the uptake of evidence-based interventions into healthcare policy and practice. While acupuncture has gained significant traction in the American healthcare landscape, its journey has been somewhat haphazard and non-linear. Methods In June 2019, a group of thirty diverse stakeholders was convened by the Society for Acupuncture Research with the support of a Patient Centered Outcomes Research Institute, Eugene Washington Engagement Award. This group of stakeholders represented a diverse mix of patients, providers, academicians, researchers, funders, allied health professionals, insurers, association leaders, certification experts, and military program developers. The collective engaged in discussion that explored acupuncture's status in healthcare, including reflections on its safety, effectiveness, best practices, and the actual implementation of acupuncture as seen from diverse stakeholder viewpoints. Objectives A primary goal was to consider how to utilize knowledge from the field of implementation science more systematically and intentionally to disseminate information about acupuncture and its research base, through application of methods known to implementation science. The group also considered novel challenges that acupuncture may present to known implementation processes. Findings This article summarizes the initial findings of this in-person meeting of stakeholders and the ongoing discussion among the subject matter experts who authored this report. The goal of this report is to catalyze greater conversation about how the field of implementation science might intersect with practice, access, research, and policymaking pertaining to acupuncture. Core concepts of implementation science and its relationship to acupuncture are introduced, and the case for acupuncture as an Evidence Based Practice (EBP) is established. The status of the field and current environment of acupuncture is examined, and the perspectives of four stakeholder groups--patients, two types of professional practitioners, and researchers--are explored in more detail.